Role of layilin in regulating mitochondria-mediated apoptosis: a study on B cell lymphoma (BCL)-2 family proteins - Mitsumi Arito; Atsuhiro Tsutiya; Masaaki Sato; Kazuki Omoteyama; Toshiyuki Sato; Yusei Motonaga; Naoya Suematsu; Manae S. Kurokawa; Tomohiro Kato (BMC Molecular and Cell Biology)
Abstract Background Malignant gliomas exhibit rapid tumor progression and resistance to treatment, leading to high lethality. One of the causes is the reduced progression of apoptosis in glioma cells. Layilin is a type 1 transmembrane protein with a C-type lectin motif in its extracellular domain. We previously reported that layilin is mainly localized to mitochondria or their close proximity and that layilin is essential for maintaining of the fragmented type of mitochondria. This study investigates the effects of layilin on mitochondria-mediated apoptosis, focusing on B cell lymphoma (BCL)-2 family proteins in a glioma cell line of A172 cells. Results We compared the levels of pro-apoptotic BCL-2 family proteins of BAD, BAK, BAX, and BIM and anti-apoptotic BCL-2 family proteins of BCL-2 and BCL-XL between layilin- knockdown (KD) cells and control cells using western blot. The protein levels of BAD were significantly smaller in layilin-KD cells than in control cells, while those of BCL-2 were significantly larger. We then compared the mitochondrial membrane potential (ΔΨm) under p-trifluoromethoxyphenyl hydrazone (FCCP)-treated conditions using MT-1 staining. In layilin-KD cells, ΔΨm was significantly larger and FCCP-induced ΔΨm reduction was significantly lower than in control cells. Furthermore, we examined the levels of cell membrane-bound Annexin V and DNA-bound propidium idodide (PI) in layilin-KD cells with/without staurosporine (STS) treatment. Layilin-KD significantly decreased levels of cell membrane-bound Annexin V with/without STS treatment. On the other hand, PI levels were not changed by layilin-KD. We also investigated the amounts of the active caspase (CASP)-3, CASP-6, CASP-7, and poly (ADP-ribose) polymerase-1 (PARP1, cleaved form), as well as DNA fragmentation in layilin-KD cells under apoptotic conditions induced by STS, using western blot and the DNA ladder method, respectively. Under STS-treated conditions, the amounts of active CASP-3, CASP-7, and poly (ADP-ribose) PARP1 were significantly smaller in layilin-KD cells than in control cells. Accordingly, DNA fragmentation was significantly suppressed in layilin-KD cells compared to control cells under STS-treated conditions. Conclusion This study demonstrates that layilin contributes to ΔΨm reduction to promote apoptosis by up-regulating BAD and down-regulating BCL-2 in glioma cells. Our data elucidates a new function of layilin: regulation of mitochondria-mediated apoptosis.